Ð’Ð»Ð¸ÑÐ½Ð¸Ðµ Ð¿Ñ€ÐµÐ¿Ð°Ñ€Ð°Ñ‚Ð¾Ð² Ð¿Ð»Ð°Ñ†ÐµÐ½Ñ‚Ñ‹ Ð½Ð° Ð¼Ð¾Ñ€Ñ„Ð¾Ñ„ÑƒÐ½ÐºÑ†Ð¸Ð¾Ð½Ð°Ð»ÑŒÐ½Ð¾Ðµ ÑÐ¾ÑÑ‚Ð¾ÑÐ½Ð¸Ðµ Ð¾Ñ€Ð³Ð°Ð½Ð¾Ð² Ð¸ Ñ‚ÐºÐ°Ð½ÐµÐ¹ ÑÑ‚Ð°Ñ€Ñ‹Ñ… ÐºÑ€Ñ‹Ñ - Perchik, O. A.; Volina, V. V. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2006)
The effect of placenta preparations: cryopreserved placenta extract (CPE) and fragment of human placenta on the organs of rats which are primarily subjected to age changes (adrenal glands, ovaries and bone tissue) is under study. It has been shown that during CPE injection to aged animals as well as during implantation to them of placental fragment there is observed the â€œrejuvenationâ€ effect manifesting in the improvement of morphofuncitonal state of parenchymatous organs